The elasticity of taxable income: A meta-regression analysis - Carina Neisser (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
The elasticity of taxable income (ETI) is a key parameter in tax policy analysis. To examine the large variation found in the literature of taxable and broad income elasticities, I conduct a comprehensive meta-regression analysis using information from 61 studies containing 1,720 estimates. My findings reveal that estimated elasticities are not immutable parameters. They are correlated with contextual factors and the choice of the empirical specification influences the estimated elasticities. Finally, selective reporting bias is prevalent, and the direction of bias depends on whether deductions are included in the tax base.
Keywords: C81; H24; H26; 330; elasticity of taxable income; income tax; behavioural response; meta-regression analysis